Gut markers for metastatic melanoma receiving immunotherapy - Guoping Ou; Juhua Gou; Hongmu Ou; Hailin Zheng; Yuanying Zhu; Jingjing Li; Xiaohua Liu (BMC Cancer)
Abstract Background This project aimed to discover independent gut markers of immunotherapy based on qPCR method. Methods 80 metastatic melanoma patients receiving immunotherapy were enrolled in this study, and the relative abundance of 41 gut markers was worked out by a newly established qPCR method. The HR of these gut markers was calculated using Rstudio-coxph. The associations between these 41 gut markers and age as well as treatment-course were analyzed by heatmap, linear-regression or VIF. Markers for Cox prediction model were selected according to the results of HR, VIF and LASSO regression. Nomogram, calibration curves for nomogram and stratified survival analysis were used to observe the predictive performance of the prediction model and related gut markers. Results BloUP may be associated with pseudoresponse of immunotherapy, especially in elderly patients. Age (risk**), treatment-type*, treatment-course (protective), clinical-response**, LDH (risk), Amc (risk**), Bvu (protective), Cpe (protective) and Rgn (risk) were recommended as predictors of immunotherapy. For patients with Age> 55 or LDH> 196, the detection of Amc could further predict the prognosis (p = 0.065, p = 0.013). For patients with Age< 55 or LDH< 196, the detection of Bvu could further predict the prognosis (p = 0.007, p = 0.011). For patients with Amc< 0.76 or Bvu > 0.84, longer treatment duration (treatment-course> 10) will significantly improve prognosis (p < 0.001, p = 0.007). AmcLOW and BvuUP marked good immunotherapy responsiveness in melanoma patients, the detection of Amc and Bvu may had potential impacts on immunotherapy strategies. Conclusions Further detection of gut markers (Amc and Bvu) could better predict patients’ responsiveness to immunotherapy.